Organizational and behavioral models in the management of patients with developmental and epileptic encephalopathy, Lennox-Gastaut syndrome and Dravet syndrome in Italy: a focus on the transition from pediatric to adult care - Di Bonaventura, Carlo; Coppola, Antonietta; Di Gennaro, Giancarlo; Corsaro, Lucio; Corsaro, Emanuele; Trivellato, Lorena; Vaccaro, Gianluca (Frontiers in Health Services, 2025)
IntroductionDevelopmental and Epileptic Encephalopathies (DEEs) are rare and complex conditions characterized by drug-resistant seizures and severe neurocognitive impairments. Management models for these disorders are often inconsistent, and the transition of care from pediatric to adult services represents a critical phase. This transition is frequently managed in an unstructured manner, leading to significant consequences for care continuity and the quality of life of both patients and their families.MethodsA cross-sectional observational survey was conducted among specialists (neurologists and pediatric neuropsychiatrists) and caregivers of patients with DEEs, particularly those diagnosed with Lennox-Gastaut Syndrome (LGS). The aim was to analyze organizational models, transition pathways, and patient and caregiver experiences, identifying existing gaps in care and comparing these models with those used for another DEE, Dravet Syndrome (DS).ResultsThe survey involved 47 physicians and 30 caregivers. Findings revealed substantial fragmentation in management models and the absence of standardized transition pathways in 54% of respondents. The transition of LGS patients to adult care centers is often left to individual families, with a dropout rate of 40% for LGS—similar to that observed in DS patients (38%). Caregivers reported stress, organizational difficulties, and a perceived decline in the quality of adult care. Furthermore, 53% of caregivers stated they received no support services following diagnosis.DiscussionThe lack of standardization in transition pathways represents a critical barrier to ensuring continuity of care for DEE and LGS patients. Developing structured, best-practice—based transition models, enhancing caregiver support, and fostering a multidisciplinary approach are essential to improve quality of life and ensure effective disease management into adulthood.